Synthesis and Investigation of Novel Optical Active SiO2 Glasses with Entrapped YAG:Ce Synthesized via Sol–Gel Method - Skruodiene, Monika; Kemere, Meldra; Inkrataite, Greta; Leimane, Madara; Ramanauskas, Rimantas; Skaudzius, Ramunas; Sarakovskis, Anatolijs (MDPI, 2023)
We present a crack-free optically active SiO2 glass-composite material containing YAG:Ce synthesized via a modified sol–gel technique. A glass-composite material consisting of yttrium aluminum garnet doped with Ce3+ (YAG:Ce) was entrapped into a SiO2 xerogel. This composite material was prepared using a sol–gel technique with modified gelation and a drying process to obtain crack-free optically active SiO2 glass. The concentration of the YAG:Ce was from 0.5 to 2.0 wt%. All synthesized samples were characterized via X-ray diffraction (XRD) and scanning electron microscopy (SEM) techniques, confirming their exceptional quality and structural integrity. The luminescence properties of the obtained materials were studied. Overall, the prepared samples’ excellent structural and optical quality makes them great candidates for further investigation, or even potential practical application. Furthermore, boron-doped YAG:Ce glass was synthesized for the first time. © 2023 by the authors. --//-- Skruodiene M., Kemere M., Inkrataite G., Leimane M., Ramanauskas R., Skaudzius R., Sarakovskis A.; Synthesis and Investigation of Novel Optical Active SiO2 Glasses with Entrapped YAG:Ce Synthesized via Sol–Gel Method; (2023) Gels, 9 (6), art. no. 488; DOI: 10.3390/gels9060488; https://www.scopus.com/inward/record.uri?eid=2-s2.0-85163728078&doi=10.3390%2fgels9060488&partnerID=40&md5=cfcfeb22fdd18ffb8bd8aa27ce54633d. Published under the CC BY 4.0 licence.
The work of Monika Skruodiene is supported by ERDF PostDoc project No.1.1.1.2/VIAA/3/19/480. The Institute of Solid State Physics, University of Latvia has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2. .
Keywords: Research Subject Categories::NATURAL SCIENCES; glass; luminescence; optical active; SiO2; sol–gel; synthesis; YAG:Ce